Adiabatic following of terahertz surface plasmon-polaritons coupler via two waveguides structure - Wei Huang (Elsevier, 2021)
Most recently, two remarkable papers (Huang et al., 2019, 2020) proposed broadband completely transferred terahertz (THz) surface plasmon-polaritons (SPPs) waveguide coupler based on coherent quantum control — Stimulated Raman adiabatic passage (STIRAP). However, these THz SPPs waveguide couplers based on the three-level quantum control technology require three SPPs waveguides, which are relatively difficult to manufacture. Hence, this paper proposes a novel broadband completely transmitted THz waveguide SPPs coupler adopting two-state adiabatic following technology. The novel coupler requires only two waveguides, which greatly reduces the manufacturing difficulty of the THz SPPs waveguide coupler. It is the first time to introduce the detuning parameter into the coupled equation of the SPPs waveguide. We believe that this discovery will further broaden the research domain of THz communication.